Mitigasi Intoleransi Melalui Kurikulum Berbasis Cinta Madrasah Ibtidaiyyah - Nadya Dwie Islami; Sheril Aulia; Shifa Galuh Chandraningtyas; Ahmad Zainuri; Frika Fatimah Zahra (Indo Publishing, 2026)
Intolerance is an increasingly complex social problem in the era of globalization, including in the Islamic education environment. Madrasah Iftidaiyah as an Islamic basic education institution has a strategic role in shaping the character of tolerant students. This study proposes mitigation of intolerance through the development of a love-based curriculum, which integrates the values of compassion, empathy, and brotherhood in everyday learning. The research method uses a qualitative approach with a case study at Madrasah Iftidaiyah XYZ, involving observation, interview, and document analysis. The results show that love-based curriculum can reduce intolerant behavior by 25% based on pre-and-post-implementation surveys. The conclusion emphasizes the importance of love education as the foundation of tolerance, with recommendations for the integration of these values into core subjects such as Aqidah Akhlak and Fiqh.